(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study aims to improve the parameterized modeling of velocity vertical profiles in coastal environments under strong tidal currents. The primary study site is the Alderney Race in Normandy, France, a macro-tidal, semi-diurnal site characterized by powerful sheared currents reaching up to 5 m/s. As part of the FloWatt project, led by HydroQuest, this site will host a pilot farm of seven tidal turbines. Ultimately, this study may simplify the representation of hydrodynamic processes at tidal energy converter deployment sites, predict vertical current shear during extreme events, and support turbine load assessments. The analytical laws traditionally used to evaluate the current rely on logarithmic or power-law formulations and are based on zero-equation turbulence closure models or partial similarity theory. These models predict velocity profiles in the bottom boundary layer well for collinear waves and currents. However, research indicates that wave-current interaction (WCI) alters the velocity profile across the entire water column. During extreme events, where waves significantly affect mean velocities, deviations from the logarithmic law are observed in the upper layers (Bennis et al., 2022). Additionally, the parameters of these analytical laws are subject to high variability, depending on factors such as bathymetry, tidal phase, and ambient turbulence, often diverging from recommended literature values (Sentchev et al., 2020). An improved logarithmic law was tested to address these difficulties, as Yang (2006) proposed. The data for this study originate from a combination of in-situ measurements and numerical modeling. In 2018, towed and mounted ADCPs were deployed in the Alderney Race as part of the Hyd2M project and HF radars were installed along the coast (Bailly du Bois et al., 2020). For the numerical part, the Coastal and Regional Ocean COmmunity model (CROCO) was coupled with the spectral wave model WAVEWATCH-III to incorporate WCI. Simulations were performed for a calm sea period (July 2018) and a winter storm period (January 2018). These simulations revealed spatial variations in model accuracy and current vertical shear, partly linked to bottom parameterization. Nevertheless, the models demonstrated good agreement near the future tidal farm. Observations and models also revealed deviations from the logarithmic law, prompting the implementation of an improved log law (Yang, 2006), which appeared to reduce discrepancies between the idealized profiles and observed/modeled data. Further work is required to correlate the newly introduced law’s parameters with waves, wind, and tides. To this end, additional numerical experiments were conducted, including scenarios with artificially amplified wave energy or reduced wind and wave conditions. These experiments confirmed that the vertical velocity profiles were significantly altered, highlighting the sensitivity of the flow dynamics to changes in external forcing.